Sulfide geochronology along the Endeavour Segment of the Juan de Fuca Ridge. (8th July 2013) - Jamieson, John W.; Hannington, Mark D.; Clague, David A.; Kelley, Deborah S.; Delaney, John R.; Holden, James F.; Tivey, Margaret K.; Kimpe, Linda E.
Abstract : [1] Forty‐nine hydrothermal sulfide‐sulfate rock samples from the Endeavour Segment of the Juan de Fuca Ridge, northeastern Pacific Ocean, were dated by measuring the decay of 226 Ra (half‐life of 1600 years) in hydrothermal barite to provide a history of hydrothermal venting at the site over the past 6000 years. This dating method is effective for samples ranging in age from ∼200 to 20, 000 years old and effectively bridges an age gap between shorter‐ and longer‐lived U‐series dating techniques for hydrothermal deposits. Results show that hydrothermal venting at the active High Rise, Sasquatch, and Main Endeavour fields began at least 850, 1450, and 2300 years ago, respectively. Barite ages of other inactive deposits on the axial valley floor are between ∼1200 and ∼2200 years old, indicating past widespread hydrothermal venting outside of the currently active vent fields. Samples from the half‐graben on the eastern slope of the axial valley range in age from ∼1700 to ∼2925 years, and a single sample from outside the axial valley, near the westernmost valley fault scarp is ∼5850 ± 205 years old. The spatial relationship between hydrothermal venting and normal faulting suggests a temporal relationship, with progressive younging of sulfide deposits from the edges of the axial valley toward the center of the rift. These relationships are consistent with the inward migration of normal faulting toward the center of the valley over time and a minimum age of onset of hydrothermal activity in this region of 5850 years. Key Points: 226Ra/Ba dating can be used to reconstruct segment scale venting history Hydrothermal venting within the Endeavour axial valley is over 3000 years old 226Ra/Ba bridges an important dating age gap between 200 to 2000 years old